Jurisdiction, recognition and enforcement in matrimonial and parental responsibility matters : a commentary on Regulation 2019/1111 (Brussels IIB) /: a commentary on Regulation 2019/1111 (Brussels IIB). (2023) - González Beilfuss, Cristina; Carpaneto, Laura; Kruger, Thalia; Pretelli, Ilaria; Župan, Mirela
No abstract available